Case Report: Rare Systemic and Aggressive ALK-Positive Histiocytosis With Recurrent Pancreatitis Treating by Alectinib - Li, Yanchu; Shi, Changle; Wu, Yu; He, Mingmin; Xia, Xueming; Liu, Jie; Jiang, Yu (Frontiers in Medicine, 2022)
ALK-positive histiocytosis (APH) is a rare and recently described, solitary or generalized, histiocytic proliferative disorder with a characteristic gene translocation involving the fusion of the ALK gene at chromosome 2p23. To date, only 25 cases of APH have been reported. It also includes solitary and systemic forms and is immunoreactive for histiocytic markers (CD68, CD163, and lysozyme) and ALK (membranous and cytoplasmic pattern). Here, we report the 26th APH case, review all previously reported cases, and discuss the clinical manifestations, genetic features, and treatment of the disease. The patient presented with multiple nodules in the lung, liver, gallbladder, pancreas, kidney, and skin rashes, along with recurrent pancreatitis and cholecystitis. The histiocytes from the lesion were positive for CD68 and ALK and negative for S100 and CD1α. A reduced dose of the ALK inhibitor alectinib was administered rather than the standard dose of alectinib or chemotherapy because of recurrent pancreatitis, which has not been previously reported in APH cases. After 18 months of follow-up, the patient was maintained on alectinib, and a partial response (PR) was achieved.